Kombinasi Buah Lada Hitam (Piper Ningrum L. ) dan Jahe Merah (Zingiber Officinale) Sebagai Cream Untuk Mengobati Penyakit Vitiligo - Fitriana Ikhtiarinawati Fajrin; Mimatun Nasihah (Poltekkes Kemenkes Padang, 2020)
Black pepper and red ginger the results of natural wealth with many benefits. The aim of this study was to determine the effectiveness of black pepper cream with red ginger combination in treating vitiligo. Using the experimental method. Data collection includes pH test, effectiveness test of black pepper cream combination of red ginger and pharmaceutical test. Data analysis used T-Paired Test to determine differences ​​area of ​​exposure before and after treatment. The pH test for the cream product resulted in a pH of 6. The pharmaceutical test explained that the cream was homogeneous, had a semi-solid form, had a distinctive odor, was brownish yellow in color and had a spreadability of 5.7 cm. The results showed that the combination of red ginger black pepper seed cream was effective in treating vitiligo with a T count value of 4.583> T table 2.131. In conclusion, there is a significant difference in the extent of vitiligo exposure to the skin before and after being given black pepper cream with red ginger combination. It is hoped that there will be further research to find out the content of black pepper and ginger which plays a role in treating vitiligo and it is hoped that the results of this study will be used as a mass-produced product and its benefits can be felt by the community, especially those with vitiligo.